2015
DOI: 10.1155/2015/625659
|View full text |Cite
|
Sign up to set email alerts
|

Serum MicroRNA Profiles Serve as Novel Biomarkers for the Diagnosis of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is the most common type of dementia, and promptly diagnosis of AD is crucial for delaying the development of disease and improving patient quality of life. However, AD detection, particularly in the early stages, remains a substantial challenge due to the lack of specific biomarkers. The present study was undertaken to identify and validate the potential of circulating miRNAs as novel biomarkers for AD. Solexa sequencing was employed to screen the expression profile of serum miRNAs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(118 citation statements)
references
References 43 publications
4
109
1
4
Order By: Relevance
“…Dong et al (2015) found that the expression of miR-93-5p in AD patients was 0.48 times that in control subjects, a finding consistent with those of the current study. Some studies have also reported the lower levels of miR-137, 181c, 9, 29a, and 29b in the serum of patients with mild cognitive impairment (Geekiyanage et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Dong et al (2015) found that the expression of miR-93-5p in AD patients was 0.48 times that in control subjects, a finding consistent with those of the current study. Some studies have also reported the lower levels of miR-137, 181c, 9, 29a, and 29b in the serum of patients with mild cognitive impairment (Geekiyanage et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…miR-9, miR-125b, and 146a were inversely expressed in CSF and serum/plasma samples from AD patients (Figure 3). Expression of miR-125b and 146a increased in the CSF and ECF serum samples from the AD patients while serum samples expression was downregulated [8485,87,90]. Similarly, the up-regulation of miR-9 expression was common in CSF, ECF, and serum samples from AD patients.…”
Section: Critical Analysis and Discussion Of Circulatory Mirna Studiesmentioning
confidence: 99%
“…In studying the use of serum as a biofluid for the analysis of circulatory miRNAs, Dong et al, examined miRNA in the sera from AD patients, individuals with MCI and vascular dementia (VD), and non-demented controls [87]. Using Solexa sequencing and RT-qPCR analysis, Dong et al identified four miRNAs that were down-regulated in the AD patients but not in any other subject group: miR-31, miR-93, miR-143, and miR-146a.…”
Section: Circulatory Mirnas In Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of miRNAs is thought to be involved in many diseases, and changes in the miRNA expression profile have been observed in cerebral ischemia and AD. Studies have demonstrated that serum miRNAs miR-93, miR-146a, and miR-31 were significantly up regulated in VaD compared to the controls; thus, they could serve as specific biomarkers to discriminate AD from VaD [65]. Endogenous circulating miRNAs have been found to be stable and consistently detected in serum, plasma and other body fluids because of their packaging and secretion into the blood within exosomes.…”
Section: Peripheral Microrna (Mirna) Profiles As Novel Biomarkersmentioning
confidence: 99%